2022
DOI: 10.1108/jfmpc-11-2021-0065
|View full text |Cite
|
Sign up to set email alerts
|

Prioritisation of resilience criteria and performance indicators for road emergencies crisis response: an analytic hierarchy process (AHP) approach

Abstract: Purpose This paper aims to develop a crisis readiness framework for road traffic crisis response for law enforcement agencies in the United Arab Emirates (UAE). Design/methodology/approach A Delphi method was used that combined questionnaire-based survey and the analytical hierarchy process to collect quantitative and qualitative data from an expert panel of crisis readiness professionals on how they prioritise and weigh the different strategic criteria, sub-criteria and performance indicators in the context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 66 publications
(102 reference statements)
0
0
0
Order By: Relevance
“…The next study from (Karl et al, 2018) with the aim of research to examine the impact of non-financial key performance indicators (KPIs) on supply chain sustainability, with the results of KPI research that significantly affect sustainability including order and delivery times, on-time delivery, supplier delivery, and customer satisfaction, further studies from (Aziz et al, 2022) The purpose of this study is to develop a road traffic accident management emergency preparedness framework for law enforcement agencies in the United Arab Emirates, the results of the study ten important aspects of emergency preparedness are identified, classified and validated. These aspects are then grouped into three distinct target groups: response planning, resources, training and coordination; information and communication management; risk and threat assessment; and early warning, legal and institutional frameworks, asset recovery and protection initiatives.…”
Section: Implementation Of Resilience With Key Performance Indicatorsmentioning
confidence: 99%
“…The next study from (Karl et al, 2018) with the aim of research to examine the impact of non-financial key performance indicators (KPIs) on supply chain sustainability, with the results of KPI research that significantly affect sustainability including order and delivery times, on-time delivery, supplier delivery, and customer satisfaction, further studies from (Aziz et al, 2022) The purpose of this study is to develop a road traffic accident management emergency preparedness framework for law enforcement agencies in the United Arab Emirates, the results of the study ten important aspects of emergency preparedness are identified, classified and validated. These aspects are then grouped into three distinct target groups: response planning, resources, training and coordination; information and communication management; risk and threat assessment; and early warning, legal and institutional frameworks, asset recovery and protection initiatives.…”
Section: Implementation Of Resilience With Key Performance Indicatorsmentioning
confidence: 99%
“…Emergency resource planning is critical to managing crisis [28]. Aziz et al [29] identified the prioritization of resilience criteria and performance indicators for road emergency crisis response, and response planning was the highest ranked criterion overall, with joint response planning and resource planning being equally prioritized sub-criteria. Zhai and Lee [10] constructed evaluation indexes for the disaster preparedness capacity of local governments, with three sub-criteria of disaster risk assessment, disaster response planning, and the preparation and approval of planning included in the planning.…”
Section: Construction Of the Evaluation Index System Of The Operation...mentioning
confidence: 99%
“…[10, [29][30][31][32][33][34][35] Demand assessment Evaluate potential demand in emergency situations and provide data support for plan formulation.…”
Section: Policy Guidancementioning
confidence: 99%
“…MCDA is designed to manage decisional processes characterised by multiple dimensions. MCDA methods, such as the Analytic Hierarchy Process (AHP) (Aziz et al, 2022;Mukesh et al, 2022;Chavoshy et al, 2018;Morshed et al, 2020), Analytic Network Process (ANP) , the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) (Tang et al, 2022b;Zhang and Ng, 2021), Principal Components Analysis (PCA) (Mohammed et al, 2022), Best-Worst method (Khan et al, 2022;Khan et al, 2023), Structural Equation Model (Zhang et al, 2022b), and Grey Relational analysis (Hu et al, 2020) are used to evaluate and rank the critical influential factors of system resilience. The fuzzy logic analysis is often used to convert qualitative descriptions of these factors into quantitative evaluation for assessing the performance of the factors (Jiao et al;Lad et al, 2022;Tang et al, 2022b) and the entropy weight method is adopted to allocate weights to the factors (Jiao et al;Li et al, 2022;Zhang and Ng, 2021).…”
Section: Mcda-based Approachesmentioning
confidence: 99%